Influence of hip strength on acl injury related biomechanics during the cutting maneuver in preadolescent students (practical implication for physical education teachers and sports pedagogues) - Petrovic, Milos; Puzovich, Vladimir; Ramos, Jorgelina; Skrkar, Stanislav; Seisenbekov, Yerlan (Pedagogy and Psychology, 2021)
Anterior cruciate ligament (ACL) injuries are one of the most serious injuries of the lower limb and can result in a relatively low rate of return to sport and decreased quality of life in later years, as well as to the psychological attitude towards sports among young people. Previous research has investigated the interaction between the hip muscles and knee valgus moments where some studies have concluded that decreased hip abductor and external rotator strength is a risk factor for ACL injury, but no research has been conducted on preadolescent population. Data from 271 students (174 girls), age 9-12 where collected while performing cutting manoeuvre and the isometric maximal voluntary contraction of hip external rotators and abductors. Our results show that no significant correlation where found between the hip strength does not influence the knee VM during the cutting manoeuvre in this age group which is in line with many previous studies conducted on older population.